Statistical error model comparison for logistic growth of green algae (Raphidocelis subcapitata). (February 2017) - Banks, H.T.; Collins, Elizabeth; Flores, Kevin; Pershad, Prayag; Stemkovski, Michael; Stephenson, Lyric
Abstract: We validate a model for the population dynamics, as they occur in a chemostat environment, of the green algae Raphidocelis subcapitata, a species that is often used as a primary food source in toxicity experiments for the fresh water crustacean Daphnia magna . We collected longitudinal data from 4 replicate population experiments with R. subcapitata . This data was fit to a logistic growth model to reveal patterns of the algae growth in a continuous culture. Overall, our results suggest that a proportional error statistical model is the most appropriate for logistic growth modeling of R. subcapitata continuous population growth.